2017
DOI: 10.1002/admi.201601088
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Fabricating Superaerophobic and Superaerophilic Surfaces

Abstract: In spite of large amount of research in fabricating surfaces of varying wettability by biomimicking the naturally occurring surfaces, the work on fundamentally and industrially important air bubble adhesion on solid surfaces and its applications are still in the burgeoning stage. The present progress report provides a discussion and a critical evaluation of the recent literature available on the fabrication of superaerophilic/superaerophobic surfaces via synergic modification of surface topography and surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 127 publications
0
83
0
Order By: Relevance
“…Adhesion of bubbles on a solid surface (patterned or smooth) is dependent on the CAH b value and the bubble volume. An idea of retentive force factor (k), contact angle hysteresis, and surface tension of liquid (γ LV ) would suffice to calculate adhesive force (F adhesion ) experienced by an air bubble on a solid surface [72] γ θ θ…”
Section: Theoretical Investigation For Gas-bubble Superwettability Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Adhesion of bubbles on a solid surface (patterned or smooth) is dependent on the CAH b value and the bubble volume. An idea of retentive force factor (k), contact angle hysteresis, and surface tension of liquid (γ LV ) would suffice to calculate adhesive force (F adhesion ) experienced by an air bubble on a solid surface [72] γ θ θ…”
Section: Theoretical Investigation For Gas-bubble Superwettability Inmentioning
confidence: 99%
“…[72] The process of gas-bubble wetting is always associated with the drainage of the wetting film around the air bubble. Benefiting from the bubble probe technique (Figure 9a), the interaction force and spatial-temporal visualization of the thin-film drainage process are measured by a combination of surface force apparatus or atomic force microscopy (AFM) and reflection interference contrast microscopy (RICM).…”
Section: Theoretical Investigation For Gas-bubble Superwettability Inmentioning
confidence: 99%
“…It has been reported that the O 2 bubbles exert a significant influence at high overpotentials at which the reac-tion is mostly limited by mass diffusiona nd transfer. [25] This surfaces trategy has been widely appliedt om odify the aerophilicity of the catalyst surfacevia tuning the gas bubbles. Improving the aerophilic behaviour at the catalysts urface has been achieved by improvingt he surfacer oughness.…”
Section: Oxygen Affinitymentioning
confidence: 99%
“…1,2 Recently, the fabrication and application of underwater superaerophobic surfaces and superaerophilic surfaces have attracted increasing interests. [1][2][3][4][5][6] An underwater superaerophobic surface generally displays a contact angle (CA) greater than 150 • to a small bubble in water, while the bubble shows the CA value smaller than 10 • on an underwater superaerophilic surface. Yong et al found that fish scales show superaerophobicity while lotus leaves show superaerophilicity in water.…”
Section: Introductionmentioning
confidence: 99%
“…15 Although some underwater superaerophobic and superaerophilic surfaces have been successfully fabricated, the related research is still at an initial stage. 1,2,[16][17][18] Those artificial materials usually have single and fixed super-wettability to underwater bubbles, either underwater superaerophobicity or underwater superaerophilicity. To obtain multifunctional applications, a smart surface that can reversibly switch between underwater superaerophobicity and superaerophilicity by a simple way is especially significant but has not been reported until now.…”
Section: Introductionmentioning
confidence: 99%